Algumas aplicações de p-pontos - Zancul, Hugo Gili (2023)
In this work we analyze the concept of \(p\)-points in \(ω\) and its relation with forcing, in particular Sacks forcing and side-by-side Sacks forcing. With this we verify that the existence of \(p\)-points with character \(\aleph_1\) is consistent with arbitrarily large \(2^{\aleph_0}\). We then analyze two applications involving \(p\)-points: the construction of a graph without unfriendly partitions and the analysis of the homogeneity of the space \(βω \setminus ω\).